Hypoglycemic and hepatoprotective activity of Phellinus fastuosus on streptozotocin-induced diabetic rats and carbon tetrachloride-intoxicated rats, respectively - Hiralal Sonawane; Deepak Shelke; Sagar Arya; Vikram Ghole; Bhaskar Behra; Subhash Gaikwad (SpringerOpen, 2024)
Abstract Background Phellinus fastuosus is a wood-eating medicinal fungus from Western Ghats of India. Therefore, we investigated hypoglycemic and hepatoprotective effects of P. fastuosus aqueous extract on streptozotocin-induced diabetic and carbon tetrachloride (CCl4) induced hepatotoxicity in rats, respectively. Result As compared to the diabetic control group, a 400 mg/kg dose had significant hypoglycemic effects, including a reduction in blood glucose (24.44%) and gain in body weight. Aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activity reduced by 31.81% and 32.84%, respectively, were also noted, along with decreases in triglycerides (24.32%) and cholesterol (25.89%) levels. The albumin, bilirubin and creatinine levels were also significantly reduced after administration of P. fastuosus extract in diabetic rats. Administration of P. fastuosus extract showed a substantial decrease in the activity of ALT, AST, alkaline phosphatase (ALP), catalase (CAT) and superoxide dismutase (SOD) in addition a decrease in the level of lipid peroxidation (LPO) as compared to CCl4-intoxicated rats. The cumulative effect of CCl4 increased the erythrocyte membrane peroxidation, whereas P. fastuosus extract reduced the cholesterol and increased phospholipid, thus preventing the alteration of membrane fluidity as compared to CCl4-intoxicated rats. FTIR and HR-LC-MS-based metabolic profiling revealed the presence of various functional groups and bioactive metabolites. Conclusion The extract showed the hypoglycemic and hepatoprotective effects due to the presence of various bioactive metabolites. Exploration of therapeutic potential of P. fastuosus using bioassay-guided fractionation is needed.